Influence of Food Environments on the Dietary Patterns of Ghanaian Immigrants in the United States: A Review - AYETTEY, Rockiy G (African Journal of Nutrition and Dietetics, 2025)
Ghanaian immigrants represent a rapidly growing share of Sub-Saharan African immigrants in the U.S., yet little is known about their dietary patterns. This literature review examined how migration and the U.S. food environment influence Ghanaian immigrants’ diets, with comparisons to peers in the U.K., Canada, and Australia. A comprehensive literature search was conducted on Ghanaian immigrants' dietary patterns and food environment in the U.S., U.K., Canada, and Australia. Findings show that dietary acculturation, U.S. food environment impact, and barriers such as access and cost influenced the dietary practices of Ghanaian immigrants and their children. The limited research highlights a critical gap in understanding the nutrition and health needs of Ghanaian immigrants in the U.S. Additional research studies focused solely on the dietary patterns of Ghanaian immigrants need to be conducted in the U.S. to gather more data on the unique food habits of Ghanaian immigrants. The additional data will help nutrition and dietary policymakers to better understand the nutritional needs and implications of Ghanaian immigrants in the U.S.